Time to initiate trophic feeding and predictors among preterm neonates admitted at General Hospitals in Tigray, 2025 - Teklebrhan Welderufael Kidane; Zeray Baraki; Asefa Iyasu; Tekle Gebremeskel Ygzaw; Binyam Gebrehiwet Tesfay; Ngsti Gebremichael Beyene; Teklewoini Mariye Zemicheal; Nebiat Desale Gidey; Geberziher Gebreslassie Welearegay (PLoS ONE, 2026)
Back ground Trophic feeding generally refers to providing small quantities of enteral feeding soon after birth. A study in Ethiopia highlighted substantial delays in starting therapeutic feeding (TF) for newborns. While guidelines recommend initiating TF within 24 hours of birth, an alarming 80–90% of infants did not begin feeding within 48 hours. Only 20% started TF within the advised timeframe. Furthermore, 29% of these infants did not survive until discharge, and 86.2% experienced extrauterine growth restriction. As a result, this study aims to assess the time to initiation of TF and its predictors among preterm neonates in the Tigray region. Method A prospective, institutional-based follow-up study was conducted on 193 preterm neonates admitted to the Neonatal Intensive Care Unit, with participants selected using systematic random sampling from a group of public hospitals.:The data collection period was from December 20, 2024, to February 30, 2025. Data was entered into Epi-Data version 4.7 and then exported to STATA version 14 for cleaning and analysis. To compare survival curves, Kaplan-Meier analysis and the log-rank test were used, bivariate and multivariate Cox regression analysis were used, all statistical tests were considered significant at a p-value of <0.05. Result A total of 193 neonates were followed for 8382 person-hours of risk time and 173 (89.6%) of neonates were initiated trophic feeding. The incidence rate of initiating trophic feeding was 2 per 100 person hours’ observations with a median time of 45 hours (95% CI: 42−56). Birth weight <1500 gram (AHR: 0.16,95% CI:0.075–0.35), APGAR score at first minute < 7 (AHR: 0.46,95% CI:0.26–0.76),APGAR score at fifth minute < 7 (AHR: 0.38,95%CI:0.21–0.68, having respiratory distress syndrome (AHR: 0.41,95% CI:0.25–0.66, and absence of Kangaroo mother care (AHR: 0.41,95% CI:0.21–0.77), were statistically Significant associated factors for the delay of initiation of trophic feeding. Conclusion In this study, a significant delay in the initiation time of trophic feeding. Therefore, health institutions should work on very low birth weight, APGAR scores below seven at one and five minutes, the presence of RDS, and the absence of KMC to shorten the initiation time and reduce complications associated with the delay.